2019
DOI: 10.1016/j.numecd.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor (HB-EGF) antisense oligonucleotide protected against hyperlipidemia-associated atherosclerosis

Abstract: Background and Aims: Heparin-binding EGF-like growth factor (HB-EGF) is a representative EGF family member that interacts with EGFR under diverse stress environment. Previously, we reported that the HB-EGF-targeting using antisense oligonucleotide (ASO) effectively suppressed an aortic aneurysm in the vessel wall and circulatory lipid levels. In this study, we further examined the effects of the HB-EGF ASO administration on the development of hyperlipidemiaassociated atherosclerosis using an atherogenic mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this scenario, plasma biomarkers, only requiring one blood sample collection, yielded promising results in the prediction of both atherosclerosis extension and/or incident CVD events (12)(13)(14)(15)(16) . Plausible biomarkers include several circulating proteins that are involved in different pathogenic steps of the atherosclerotic plaque development, such as matrix metalloproteinases (MMPs) (17)(18)(19) , smooth muscle cells (SMC) (20)(21)(22)(23) and endothelial cells (EC) (20,(24)(25)(26)(27) growth factors (GFs), as well as mediators of apoptosis (20,(28)(29)(30)(31) and inflammation (20,32,33) . However, available studies focused on small subsets of these biomarkers and/or did not consider the complex interrelationship among them.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, plasma biomarkers, only requiring one blood sample collection, yielded promising results in the prediction of both atherosclerosis extension and/or incident CVD events (12)(13)(14)(15)(16) . Plausible biomarkers include several circulating proteins that are involved in different pathogenic steps of the atherosclerotic plaque development, such as matrix metalloproteinases (MMPs) (17)(18)(19) , smooth muscle cells (SMC) (20)(21)(22)(23) and endothelial cells (EC) (20,(24)(25)(26)(27) growth factors (GFs), as well as mediators of apoptosis (20,(28)(29)(30)(31) and inflammation (20,32,33) . However, available studies focused on small subsets of these biomarkers and/or did not consider the complex interrelationship among them.…”
Section: Introductionmentioning
confidence: 99%
“…VLDL can transport hepatic TG into the blood stream; therefore, the enhancement of hepatic VLDL secretion may protect the liver from TG accumulation (Agnes et al., 2004; Wang et al., 2016). TG, which circulates to the extra‐hepatic tissues via the circulatory system, can be catabolised into fatty acids and glycerol under the action of lipoprotein lipase and hormone‐sensitive lipase, or it is directly oxidised into carbon dioxide and water to release energy (Agnes et al., 2004; Kim et al., 2019). Furthermore, it was also detected that the choline supplemented did not change the serum LDL‐C levels of ducks, and there was no correlation between the serum VLDL and LDL‐C levels, indicating that the increased VLDL levels did not promote the synthesis of LDL‐C, a causal risk factor for AS.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA participates in the formation of atherosclerosis by regulating autophagy in endothelial cells, smooth muscle cells, and macrophages ( Ren et al, 2020 ). Studies have shown that lncRNA can be associated with cholesterol deposition and macrophage-mediated inflammation ( Yan et al, 2020 ), which will provide a reference for antisense oligonucleotide therapy of atherosclerosis ( Graham et al, 2017 ; Kim et al, 2019 ). Exosome is a vital carrier to maintain cell homeostasis and transfer intercellular information ( Tian et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%